The aneurogenic limb identifies developmental cell interactions underlying vertebrate limb regeneration (2011)
ABSTRACT: The removal of the neural tube in salamander embryos allows the development of nerve-free aneurogenic limbs. Limb regeneration is normally nerve-dependent, but the aneurogenic limb regenerates without nerves and becomes nerve-dependent after innervation. The molecular basis for these tissue interactions is unclear. Anterior Gradient (AG) protein, previously shown to rescue regeneration of denervated limbs and to act as a growth factor for cultured limb blastemal cells, is expressed throughout the larval limb epidermis and is down-regulated by innervation. In an aneurogenic limb, the level of AG protein remains high in the epidermis throughout development and regeneration, but decreases after innervation following transplantation to a normal host. Aneurogenic epidermis also shows a fivefold difference in secretory gland cells, which express AG protein. The persistently high expression of AG in the epithelial cells of an aneurogenic limb ensures that regeneration is independent of the nerve. These findings provide an explanation for this classical problem, and identify regulation of the epidermal niche by innervation as a distinctive developmental mechanism that initiates the nerve dependence of limb regeneration. The absence of this regulation during anuran limb development might suggest that it evolved in relation to limb regeneration.